2016
DOI: 10.1259/bjr.20160342
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body cardiovascular MRI for the comparison of atherosclerotic burden and cardiac remodelling in healthy South Asian and European adults

Abstract: Objective:To determine the feasibility of using whole-body cardiovascular MRI (WB-CVMR) to compare South Asians (SAs)—a population known to have a higher risk of cardiovascular disease (CVD) but paradoxically lower prevalence of peripheral arterial disease—and Western Europeans (WEs).Methods:19 SAs and 38 age-, gender- and body mass index-matched WEs were recruited. All were aged 40 years and over, free from CVD and with a 10-year risk of CVD <20% as assessed by the adult treatment panel (ATP) III risk score. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Besides symptomatic PAD patients, MRI has also been used to examine peripheral arterial plaques in non-symptomatic subjects. In 2018, Weir-McCall et al found that compared to Western Europeans, South Asians have a lower iliofemoral plaque burden [ 90 ]. In the same year, Han et al discovered that subclinical femoral artery atherosclerosis is prevalent in the elderly population [ 75 ], particularly in the left femoral artery and segments of the common femoral artery and popliteal artery.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Besides symptomatic PAD patients, MRI has also been used to examine peripheral arterial plaques in non-symptomatic subjects. In 2018, Weir-McCall et al found that compared to Western Europeans, South Asians have a lower iliofemoral plaque burden [ 90 ]. In the same year, Han et al discovered that subclinical femoral artery atherosclerosis is prevalent in the elderly population [ 75 ], particularly in the left femoral artery and segments of the common femoral artery and popliteal artery.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Furthermore, the onset of coronary heart disease is earlier in South Asian people [4,5]. This may be indicative of ethnic differences in vascular remodelling [6,7]. There are also ethnic differences in healthcare-seeking behaviour and the way doctors manage South Asian people with chest pain [8][9][10].…”
Section: Introductionmentioning
confidence: 99%